The effects of shuttle run and three corner drill on the agility of soccer players in soccer academy - Nawan Primasoni; Donny Mahendra Prakosa; Tama Anugrah (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
Football is a game that is played by kicking the ball to get the ball into the opponent's goal. The game of soccer requires speed and agility. This study aims to determine the effects of shuttle runs and three corner drills on agility and to compare the effect of those exercises on the agility of twenty soccer players in the Soccer Academy. This experimental research employed the two groups of pretest-posttest design. The population used is a Kalasan soccer academy player with a total of 20 players. The sample used is the entire population and will be divided into two groups with an ordinal pairing technique. The soccer players' agility was assessed using the Illinois agility test in the pretest and post-test. Shuttle run and three corner drill exercises were carried out 16 times (3 times a week). Based on the results of data analysis, the average pretest score of the shuttle run group is 17.99, while the post-test average score is 16.15. Then, the average scores of the three corner drill groups are 18.08 and 16.32, respectively in the pretest and post-test. The pretest and post-test scores of both groups were compared, and the differences are 1.84 seconds for the shuttle run and 1.76 seconds for the three-corner drill. This study concludes that the shuttle run and three corner drill are both significantly effective in improving agility because those exercises are not significantly different, but the shuttle run works better than the three corner drill in improving agility.